Efficacy and Safety of Initial 5 Years of Adjuvant Endocrine Therapy in Postmenopausal Hormone Receptor-Positive Breast Cancer: A Systematic Review and Network Meta-Analysis - Liao, Hao; Pei, Wendi; Zhong, Jianxin; Shao, Bin; Liu, Xiaoran; Liu, Yaxin; Zhang, Jiayang; Rugo, Hope S.; Li, Huiping (Frontiers in Pharmacology, 2022)
Purpose: To identify the optimal initial 5 years of adjuvant endocrine therapy for hormone receptor-positive postmenopausal early breast cancer (EBC) patients. Methods: We conducted a systematic search of the PubMed, Web of Science, and EMBASE to obtain relevant studies published between January 2000 and January 2022. Randomized clinical trials assessing the efficacy and safety of initial 5 years of adjuvant endocrine therapy were included. The primary outcomes were disease-free survival and overall survival and the secondary outcome was severe adverse effects (SAEs). A Bayesian network meta-analysis was carried out to indirectly compare all regimens and the value of surface under the cumulative ranking curve (SUCRA) was used to obtain rankings. Results: Eleven studies with 49,987 subjects were included. For DFS, exemestane (EXE) [hazard ratio (HR) 0.91, 95% confidence interval (95%CI) 0.87–0.96], anastrozole (ANA) (0.94, 0.90–0.97), letrozole (LET) (0.93, 0.89–0.97), tamoxifen (TAM) followed by EXE (0.91, 0.87–0.96), and TAM followed by ANA (0.92, 0.87–0.98) were more favorable than TAM, with TAM followed by EXE ranking as the first of SUCRA. For OS, only TAM followed by ANA showed significant superiority than TAM (HR 0.91, 95%CI 0.86–0.97) and ranked as the first of SUCRA. For SAEs, EXE (HR 1.72, 95%CI 1.04–2.98), ANA (1.58, 1.03–2.43), and LET (1.63, 1.02–2.57) showed greater associations with bone fracture than TAM. However, no significant difference in the incidences of cardiac events, thromboembolic events, and cerebrovascular events was found among all comparisons. Conclusion: The sequential use of aromatase inhibitors, which has the best curative effects and relatively mild side effects, may be the optimal treatment mode for hormone receptor-positive postmenopausal EBC patients. In addition, the three kinds of aromatase inhibitors achieved roughly equal efficacy, but caused different types of SAEs. Systematic Review Registration: [website], identifier [registration number].